Planar high rejection dual band-notch UWB antenna with X & Ku-bands wireless applications. Issue 8 (2nd May 2017) - Sharma, Manish; Awasthi, Yogendra Kumar; Singh, Himanshu
Abstract : In this paper, a vase-shaped monopole antenna is presented for dual band notch (WiMAX IEEE802.16 3.30–3.80 GHz with C-band 3.80–4.20 GHz and WLAN IEEE802.11a/h/j/n 5.15–5.35 GHz, 5.25–5.35 GHz, 5.47–5.725 GHz, 5.725–5.825 GHz) UWB and other wireless services (close range radar: 8–12 GHz in X-band & satellite communication: 12–18 GHz in Ku-band). Measured VSWR of proposed antenna shows a high band-rejection for WiMAX along with C-band with VSWR = 25.33 at 3.77 GHz and WLAN with VSWR = 6.0 at 5.64 GHz is achieved by cutting two C-shaped slots on the radiating patch. Designed antenna covers a wide usable fractional bandwidth 160% (2.58–20.39 GHz). Furthermore, the measured gain of antenna is relatively stable across the impedance bandwidth except band-notched. In addition, antenna offers omni-directional pattern, reasonably small 20 × 20 × 0.787 mm 3 and easy to construct structure.